The Relationship Between Employment Opportunity and the Standard of Living as a Result of Population Mobility - Sari, Rahma Mutiya; Wahyuni, Ekawati Sri; Nurdinawati, Dina (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
Indonesian labor  market continues to develop, it is proved by the increase in the number of jobs and the growth of open unemployment. Job opportunities not only in urban areas but also in the rural areas. Employment opportunities in rural areas could be open due to many  factors, one of them  for their arrivals to the region. The purpose of this research is to analyze the relationship between  employment opportunity with the standard of living because of population mobility.  Employment opportunity divided in to job sectors, job types, and job status. The standard of living divided in to primer, secunder, and tertiary. This research use quantitative and qualitative methods. The result shows that  employment opportunity open because the population mobility become an opportunity for people to improve the standard of living.  Keyword: Employment Opportunity, population mobility, the standard of living=============================================== ABSTRAKPasar tenaga kerja Indonesia terus mengalami perkembangan, hal ini terbukti dengan peningkatan jumlah pekerjaan dan penurunan angka pengangguran terbuka. Kesempatan kerja teryata tidak hanya terjadi di perkotaan, tetapi juga terjadi di pedesaan. Kesempatan kerja yang terbuka di pedesaan dapat terjadi karena banyak faktor, salah satunya karena adanya pendatang ke suatu wilayah. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara kesempatan kerja dengan taraf hidup masyarakat karena adanya pendatang. Kesempatan kerta terbagi menjadi tiga, sektor/lapangan pekerjaan, jenis/jabatan pekerjaan, dan status pekerjaan. Taraf  hidup telah dikelompokkan menjadi taraf hidup primer, sekunder, dan tersier. Penelitian ini dilakukan dengan pendekatan kuantitatif dan kualitatif. Hasil dari penelitian ini menunjukkan bahwa terbukanya kesempatan kerja karena adanya pendatang menjadi peluang bagi masyarakat guna meningkatkan taraf hidup.Kata kunci: gerak penduduk, kesempatan kerja, taraf hidup